Superhydrophobic Tipped Antimicrobial Photodynamic Therapy Device for the In Vivo Treatment of Periodontitis Using a Wistar Rat Model - Tonon, Caroline Coradi (2023)
Limited options exist for treatment of periodontitis; scaling and root planing (SRP) are not sufficient to eradicate P. gingivalis and the resulting inflammatory disease. Chlorhexidine (CHX), used as an adjuvant to SRP, may reduce bacterial loads but leads to pain and staining, while evidence for its efficacy is lacking. Antibiotics are effective but can lead to drug-resistance. The rising concern of antibiotic resistance limits the future use of this treatment approach. This study evaluates the efficacy of a novel superhydrophobic (SH) antimicrobial photodynamic therapy (aPDT) device as an adjuvant to SRP for the treatment of periodontitis induced in a Wistar rat in vivo model relative to CHX. The SH-aPDT device comprises an SH silicone rubber strip coated with verteporfin photosensitizer (PS), sterilized, and secured onto a tapered plastic optical fiber tip connected to a red diode laser. The superhydrophobic polydimethylsiloxane (PDMS) strips were fabricated by using a novel soluble template method that creates a medical-grade elastomer with hierarchical surface roughness without the use of nanoparticles. Superhydrophobicity minimizes direct contact of the PS-coated surface with bacterial biofilms. Upon insertion of the device tip into the pocket and energizing the laser, the device generates singlet oxygen that effectively targets and eliminates bacteria within the periodontal pocket. SH-aPDT treatment using 125 J/cm2 of red light on three consecutive days reduced P. gingivalis significantly more than SRP-CHX controls (p < 0.05). Clinical parameters significantly improved (p < 0.05), and histology and stereometry results demonstrated SH-aPDT to be the most effective treatment for improving healing and reducing inflammation, with an increase in fibroblast cells and extracellular matrix and a reduction in vascularization, inflammatory cells, and COX-2 expression. The SH-aPDT approach resulted in complete disease clearance assessed 30 days after treatment initiation with significant reduction of the periodontal pocket and re-formation of the junctional epithelium at the enamel-cementum junction. PS isolation on a SH strip minimizes the potential for bacteria to develop resistance, where the treatment may be aided by the oxygen supply retained within the SH surface.